Effects of Jigsaw IV Strategy on Academic Achievement and Retention in Digestive System and Feeding Mechanism among Secondary School Biology Students in Kano-Nigeria - Bello, Safiyya Sa’id; Mukhtar, Nasiru (Faculty of Natural and Applied Sciences Journal of Mathematics, and Science Education, 2025)
Considerable errors were observed in the performance of Biology students by WAEC Chief Examiners in their various reports, including poor spelling of technical terms, inability to name the illustrated diagrams of organisms, and inability to describe the process of conversion of food to chime. These errors cause low performance in the students’ overall result of Biology. As a consequence, this study investigated the effects of J4CLS on academic achievement and retention in digestive system and feeding mechanism among Biology students in science secondary schools in Kano State, Nigeria. The study adopted pre-test, post-test and post-post-test quasi-experimental design. The population of the study consisted of 3402 SS II Biology students (1468 males and 1934 females), while the sample of the study consisted of 216 subjects from four intact classes drawn through stratified random sampling technique. Digestive System Achievement Test (DSAT) with reliability index of 0.94 was used as instrument of data collection. The result of the study revealed that Biology students taught using J4CLS performed and retained better than their counterpart taught using lecture method of teaching (Mean gain for J4CLS is 25.82 as against 12.57 for Lecture Method group; p=0.000<0.05). It was also discovered that female students performed better than their male counterpart (Mean gain for Female is 24.48 as against 27.14 for Male; p=0.032>0.05), but gender was not a significant factor in the retention of Biology students taught using J4CLS. It was recommended among others that school authorities should encourage Biology teachers to adopt J4CLS in their classrooms.